Effect of Uric Acid Control on Serum Creatinine. Issue 7 (October 2019) - Yamamoto, Ted; Xie, John; Li, Zhongze; Field, Carey; Block, Clay; Taylor, Thomas
Abstract : Objective: Hyperuricemia has been epidemiologically associated with multiple comorbidities including chronic renal failure and cardiovascular disease. Cause and effect are difficult to address, given comorbidities associated with and prevalence of metabolic syndrome. One impediment to achieving serum uric acid (sUa) levels less than or equal to 6.0 mg/DL is the concept that allopurinol might be nephrotoxic. We examined the relation of sUa less than or equal to 6.0 mg/dL to renal function over time. Methods: This is a medical records review study of 348 hyperuricemia patients identified in 2015, as having been followed with serial uric acid measurements. After 1 year of serial urate levels, to allow for treatment, patient cohorts were defined: sUa less than or equal to 6.0 mg/dL and sUa greater than 6.0 mg/dL. A repeated measure model was used to test for an association between uric acid level and serum creatinine, while adjusting for covariates. Results: There was a significant difference in the least square means of serum creatinine comparing those who achieved an sUa less than or equal to 6.0 mg/dL versus sUa greater than 6.0 mg/dL (1.39 mg/dL [95% confidence interval, 1.30–1.48] vs 1.57 mg/dL [95% confidence interval, 1.46–1.69]; p = 0.0015). This is a between-group difference in creatinine of 0.18 mg/dL. If a change in serum creatinine of 0.2 is considered significant, this short-term between-group progression of renal failure approaches clinical significance. Conclusions: Given that most serial measures were within the first few years of follow-up, and change in renal function occurs slowly over time, the between group difference of sUa of 0.18 mg/dL is close to a clinically significant creatinine difference of 0.2 mg/dL.